Mourning Women, the Voice of God, and the Limits of Lament: Women’s Songs of Lament in Jeremiah - Wray Beal, Lissa M. (Bulletin for biblical research, 2023)
The book of Jeremiah contains metaphors depicting Israel and Zion as a woman. These include the city as a mourning woman (4:19-21; 10:20). Real mourning women are addressed in Jer 9:17-22, following laments variously attributed to Jeremiah and/or Yahweh (8:18-9:2, 10). Working with the (MT) canonical form and engaging the insights of trauma studies, this article traces linguistic and thematic connections between the two passages before tracing similar connections to Rachel’s lament (Jer 31). The mourning women in Jer 9 serve a societal role by giving voice to lament; this effective power is affirmed by trauma studies. When read alongside the lament by Jeremiah and/or Yahweh, this article notes the women also take up a prophetic role as with Jeremiah they embody and express Yahweh’s own pathos. In ch. 31, the mourning women are metaphorically instantiated in the eponymous mother who also voices Yahweh’s pathos yet remains uncomforted. This study points to the hope that arises from Yahweh’s identification with his people in the pathos expressed by prophet, mourning women, and Rachel. Ultimately, Yahweh’s identification with his people, and his words of hope offer comfort to unrequited lament.